Reconstruction of Symptomatic Congenital Anterior Cruciate Ligament Insufficiency. Issue 2 (February 2019) - Sachleben, Brant C.; Nasreddine, Adam Y.; Nepple, Jeffrey J.; Tepolt, Frances A.; Kasser, James R.; Kocher, Mininder S.
Abstract : Background: Hypoplasia or congenital absence of the anterior cruciate ligament (ACL) is a rare disorder occurring in ∼1 in every 6000 births. Although some patients with hypoplasia or agenesis of the ACL may not complain of instability, others desire to participate in more demanding activities that require the stability of a competent ACL. There are limited reports of surgical treatment of this patient population. The purpose of this study was to report ACL reconstruction in a case series of patients with symptomatic congenital ACL deficiency. Methods: A retrospective medical record review of the surgical treatment of 14 knees (13 patients) with congenital absence of the ACL at a tertiary care institution from 1995 to 2012 was performed. Patients with a minimum of 1 year of clinical follow-up were eligible for inclusion. Results: The mean age at time of surgery was 12.6 (range, 3 to 22), including 6 patients <12 years of age. Mean follow-up was 2.9 years (range, 1 to 6.6). Nine of 13 patients (69%) had underlying congenital abnormalities/associated syndromes. Preoperative Lachman and pivot shift examination was International Knee Documentation Committee grade C or D in all but 1 knee. ACL reconstruction was performed with combined intra-articular/extra-articular physeal sparing reconstruction with iliotibial band (n=5), autograft hamstring (n=2) or bone-patellar tendon-bone (n=3), or allograft (n=4). Multiligament reconstruction of associated ligamentous deficiency was performed in 7 knees (50%). Postoperative Lachman and pivot shift testing was International Knee Documentation Committee (IKDC) grade A or B in all but 1 knee. One patient with congenital absence of multiple knee ligaments required revision ACL reconstruction surgery, with concurrent first-time posterior cruciate ligament reconstruction, due to persistent instability. None required revision surgery due to graft tear at a minimum of 1-year follow-up. Conclusions: Surgical stabilization of symptomatic congenital ACL insufficiency, with associated ligamentous reconstruction as required on a case-by-case basis, results in improved stability at early clinical follow-up, with low complication rates. Level of Evidence: Level IV—retrospective case series.